Genome-Wide Analysis of Glioblastoma Patients with Unexpectedly Long Survival. Issue 6 (29th March 2019) - Richardson, Timothy E; Patel, Seema; Serrano, Jonathan; Sathe, Adwait Amod; Daoud, Elena V; Oliver, Dwight; Maher, Elizabeth A; Madrigales, Alejandra; Mickey, Bruce E; Taxter, Timothy; Jour, George; White, Charles L; et al.
Abstract: Glioblastoma (GBM), representing WHO grade IV astrocytoma, is a relatively common primary brain tumor in adults with an exceptionally dismal prognosis. With an incidence rate of over 10 000 cases in the United States annually, the median survival rate ranges from 10–15 months in IDH1/2 -wildtype tumors and 24–31 months in IDH1/2 -mutant tumors, with further variation depending on factors such as age, MGMT methylation status, and treatment regimen. We present a cohort of 4 patients, aged 37–60 at initial diagnosis, with IDH1 -mutant GBMs that were associated with unusually long survival intervals after the initial diagnosis, currently ranging from 90 to 154 months (all still alive). We applied genome-wide profiling with a methylation array (Illumina EPIC Array 850k) and a next-generation sequencing panel to screen for genetic and epigenetic alterations in these tumors. All 4 tumors demonstrated methylation patterns and genomic alterations consistent with GBM. Three out of four cases showed focal amplification of the CCND2 gene or gain of the region on 12p that included CCND2, suggesting that this may be a favorable prognostic factor in GBM. As this study has a limited sample size, further evaluation of patients with similar favorable outcome is warranted to validate these findings.